The step further smile virtual planning: milled versus prototyped mock-ups for the evaluation of the designed smile characteristics - Antonino Lo Giudice; Luca Ortensi; Marco Farronato; Alessandra Lucchese; Erica Lo Castro; Gaetano Isola (BMC, 2020)
Abstract Background Mock-up based approach allows the preview of the aesthetic rehabilitation, however, it is crucial that the mock-up does not differ from the expected aesthetic outcomes. With CAD-CAM technologies, it is possible to directly create mock-ups from virtual planned smile project, with greater accuracy and efficiency compared to the conventional moulded mock-ups. In this study, we investigated the trueness of mock-ups obtained with milling and 3D printing technology and a full digital work-flow system. Methods Ten adults subjects were included and digital smile design/digital wax-up were performed to enhance the aesthetic of maxillary anterior region. Ten milled mock-ups and 10 prototyped mock-ups were obtained from the original .stl file and a digital analysis of trueness was carried out by superimposing the scanned-milled mock-ups and the scanned-prototyped mock-ups to the digital wax-up, according to the surface-to-surface matching technique. Specific linear measurements were performed to investigate and compare the dimensional characteristics of the physical manufactures, the 3D project and the scanned mock-ups. All data were statistically analyzed. A clinical test was also performed to assess the fitting of the final manufacture. Results The prototyped mock-ups showed a significant increment of the transversal measurements (p < 0.001) while the milled mock-ups showed a significant increment of all vertical and transversal measurements (p < 0.001). The prototyped mock-ups showed good fitting after clinical tests while none of the milled mock-ups showed good adaptation (no fitting or significant clinical compensation required). Deviation analysis from the original 3D project reported a greater matching percentage for the scanned-milled mock-ups (80,31% ± 2.50) compared to the scanned-prototyped mock-ups (69,17% ± 2.64) (p < 0.001). This was in contrast with the findings from linear measurements as well as from the clinical test and may have been affected by a reductive algorithmic computation after digitization of physical mock-ups. Conclusion Both prototype and milled mock-ups showed a slight dimensional increment comparing to the original 3D project, with milled-mock-ups showing less fitting after clinical tests. Caution must be taken when assessing the trueness of scanned manufacture since an intrinsic error in the system can underestimate the dimensions of the real object.